2022
DOI: 10.1155/2022/2538896
|View full text |Cite
|
Sign up to set email alerts
|

The Fusion Application of Deep Learning Biological Image Visualization Technology and Human-Computer Interaction Intelligent Robot in Dance Movements

Abstract: The paper aims to apply the deep learning-based image visualization technology to extract, recognize, and analyze human skeleton movements and evaluate the effect of the deep learning-based human-computer interaction (HCI) system. Dance education is researched. Firstly, the Visual Geometry Group Network (VGGNet) is optimized using Convolutional Neural Network (CNN). Then, the VGGNet extracts the human skeleton movements in the OpenPose database. Secondly, the Long Short-Term Memory (LSTM) network is optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The last problem is the situation of research events at the state of the technology with the technology that is used for the assessment of the participant and on the table data gathered from groups of seven students, 'size predisposition technology' section, the highest value in M = 4.36 out at the same time as high technology 'media use' (M = 2.08), it is noted that this situation is examined in Table 7, when the size of the technology that is used for local activities in biological studies the tendency of abstinence it can be said that their status is low, the situation is very good. Jin, Wen, and Xie's (2022) in the year they have done research in the biological, recognise and analyse deep learning-based image visualisation technology applications and biological studies in this research are aimed at local system as a result of deep learning-based interactive visualisation created a high rate of accuracy is higher, and learning-based image visualisation technology that has tremendous potential, it is seen that the conclusion reached in human movement. In this context, when this value is combined with the results of the research, it is observed that the biological local study situations are shaped by technology and at the same time it is concluded that this dimension gains meaning with technology.…”
Section: The Status Of the Groups Of Participants Participating In Th...mentioning
confidence: 99%
“…The last problem is the situation of research events at the state of the technology with the technology that is used for the assessment of the participant and on the table data gathered from groups of seven students, 'size predisposition technology' section, the highest value in M = 4.36 out at the same time as high technology 'media use' (M = 2.08), it is noted that this situation is examined in Table 7, when the size of the technology that is used for local activities in biological studies the tendency of abstinence it can be said that their status is low, the situation is very good. Jin, Wen, and Xie's (2022) in the year they have done research in the biological, recognise and analyse deep learning-based image visualisation technology applications and biological studies in this research are aimed at local system as a result of deep learning-based interactive visualisation created a high rate of accuracy is higher, and learning-based image visualisation technology that has tremendous potential, it is seen that the conclusion reached in human movement. In this context, when this value is combined with the results of the research, it is observed that the biological local study situations are shaped by technology and at the same time it is concluded that this dimension gains meaning with technology.…”
Section: The Status Of the Groups Of Participants Participating In Th...mentioning
confidence: 99%
“…Zhu et al [22] has discussed the Dance Action Recognition and Pose Estimation based on Deep Convo-lutional Neural Network (DCNN) uses a deep learning model to recognize dance actions and estimate pose from a sequence of frames. The deep learning model consists of a convolutional neural network (CNN) and a long short-term memory (LSTM) network.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few researchers studying the composition of wheeled robot dance, and most of them only focus on the beauty of robot dance, neglecting an important factor in dance, which is dance composition (Taubes, 2000 ; Bryant et al, 2017 ; Jin et al, 2022 ; Su et al, 2023 ). Dance composition not only enhances the overall beauty of the dance but also is an essential factor in expressing the theme of the work.…”
Section: Introductionmentioning
confidence: 99%